Evaluasi Penggunaan Model Pembelajaran Mind Mapping pada Mata Kuliah Desain Ilustrasi - Annisau Nafiah; Agus Hery; Hapsari Kusumawardani (Jurnal Inovasi Teknologi dan Edukasi Teknik, 2021)
Mind mapping learning models are often used in adaptive and normative learning. In this study, the researcher will evaluate the implementation of the mind mapping learning model that is integrated into practical learning in the illustration design course. In the illustration design course, students emphasize making fashion design. The mind mapping learning model is implemented when students are looking for ideas or concept that will be used as inspiration making fashion design. The purpose of this study is to describe the application of the mind mapping learning model in the illustration design course. This research method uses quantitative descriptive using a sample of 95 students. Based on the research results, it shows that the mind mapping learning models are very helpful for students in determining ideas or themes as their source of inspiration. The mind mapping learning model can also improve student skills in making mood board and storyboard collages as a reference in fashion design cantering so as not to deviate from a predetermined theme. The conclusion that can be drawn from this research is that the mind mapping learning model can improve student's cognitive and psychomotor abilities in learning illustration design practice. Model pembelajaran mind mapping sering kali digunakan dalam pembelajaran adaptif dan normatif. Pada penelitian ini, peneliti akan mengevaluasi penerapan model pembelajaran mind mapping yang diintegrasikan ke dalam pembelajaran praktik pada mata kuliah desain ilustrasi. Pada mata kuliah desain ilustrasi, mahasiswa ditekankan pada pembuatan desain busana. Model pembelajaran mind mapping diimplementasikan ketika mahasiswa sedang mencari ide atau konsep yang akan dijadikan sebagai inspirasi dalam membuat desain busana tersebut. Tujuan dari penelitian ini adalah mendeskripsikan penerapan model pembelajaran mind mapping pada mata kuliah desain ilustrasi. Metode penelitian ini menggunakan deskriptif kuantitatif dengan menggunakan sampel sebanyak 95 mahasiswa. Berdasarkan hasil penelitian menunjukkan bahwa model pembelajaran mind mapping sangat membantu mahasiswa dalam menentukan ide atau tema sebagai sumber inspirasinya. Model pembelajaran mind mapping juga dapat meningkatkan keterampilan mahasiswa dalam membuat moodboard dan storyboard sebagai acuan dalam pembuatan desain busana agar tidak menyimpang dari tema yang telah ditentukan. Simpulan yang dapat diambil dari penelitian ini adalah model pembelajaran mind mapping dapat meningkatkan kemampuan kognitif dan psikomotorik mahasiswa dalam pembelajaran praktek desain ilustrasi.